Approximately cubic funtional equations and cubic multipliers. - Bodaghi, Abasalt; Alias, Idham Arif; Ghahramani, Mohammad Hossein (Springer Open, 2011)
In this paper, we prove the Hyers-Ulam stability and the superstability for cubic functional equation by using the fixed point alternative theorem. As a consequence, we show that the cubic multipliers are superstable under some conditions.